Method for reducing coating difficulty of lithium-rich lithium ferrite in pole piece homogenate coating process
By coating lithium-rich lithium ferrate with carbon source and non-metal oxide and sintered at high temperature, the coating difficulty and battery performance problems are solved, more uniform coating and higher air stability are achieved, and lithium-ion batteries are ensured. electrochemical properties.
Patent Information
- Application Number
- CN202411358117.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium-rich lithium ferrate is prone to form micelles during the homogenization of the electrode sheet, resulting in difficult coating and degradation of battery performance. The prior art hydrophobic coating or hydrolysis methods have side reactions and material deterioration problems.
The carbon source and non-metal oxide are used to coat lithium lithium ferrate at the same time, and the surface residual alkali is reduced during high-temperature sintering treatment to improve coating uniformity and air stability.
It significantly reduces the difficulty of coating, improves coating uniformity and electrochemical properties, extends the air stability of the material, and ensures that the first-time charging specific capacity of the battery remains above 690mAh/g.
Smart Images

Figure CN119208568A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for reducing the difficulty of coating lithium-rich lithium ferrite during the slurry coating process of pole pieces. Background Art
[0002] During the first charge and discharge process of lithium-ion batteries, it is inevitable that the organic electrolyte will be reduced and decomposed on the surface of the negative electrode to form a solid electrolyte interface film and lithium oxide, which will make a large number of lithium ions lose their activity and become "dead lithium", consuming the lithium ions in the positive electrode material, resulting in a decrease in the first cycle coulomb efficiency (ICE) of the battery, affecting the improvement of the battery's specific energy. Positive electrode lithium supplement additives have attracted much attention because they can irreversibly migrate excess lithium ions to the negative electrode to compensate for the loss of active lithium in the negative electrode material.
[0003] The charge and discharge platform of lithium-rich lithium iron oxide Li5FeO4 (LFO) is 3.5-4.0V, and its theoretical specific capacity is as high as 867mAh / g, so it has very good application prospects. However, pure lithium-rich lithium iron oxide is prone to flocculent during the electrode slurry coating process due to excessive residual alkali on the surface, which affects the uniformity of the electrode coating and further affects the subsequent electrochemical performance test.
[0004] In order to solve the above problems, it is crucial to propose a method to improve the difficulty of coating. The prior art mostly adopts the method of introducing a hydrophobic coating layer / isolation layer or a hydrolysis method. The former can contain the residual alkali inside the material, improve the slurry stability and air stability, but because the residual alkali still exists inside the material, it is inevitable to contact with the electrolyte when the battery is working, catalyzing the side reactions of the electrolyte, increasing gas production and deteriorating battery performance. The latter dissolves the material in the reagent, reduces the surface residual alkali through a hydrolysis reaction, and thus reduces the difficulty of its slurry coating. However, since most of the reagents used are liquids, the water in the liquid will react with the lithium-rich lithium iron oxide, which will also cause the material to deteriorate. Summary of the invention
[0005] The present invention provides a method for reducing the difficulty of coating lithium-rich lithium iron oxide during the slurry coating process of the electrode. The method creatively uses a carbon source and a non-metallic oxide to simultaneously coat the lithium-rich lithium iron oxide for the first time, thereby solving the problem of floccules and a sharp drop in battery performance of pure lithium-rich lithium iron oxide during slurry coating, making it easier to coat and having coating uniformity. In addition, the coating layer of the carbon source and the non-metallic oxide can slow down the water absorption and deterioration of the lithium-rich lithium iron oxide in the air to a certain extent, thereby improving the air stability of the lithium-rich lithium iron oxide.
[0006] In order to achieve the above object, the present invention provides a method for reducing the difficulty of coating lithium-rich lithium iron oxide during the slurry coating process of the pole piece, comprising the following steps:
[0007] In a special environment where the air humidity is below 10%, the prepared lithium-rich lithium ferrite is mixed only with a carbon source and a non-metallic oxide to obtain a mixed material.
[0008] The above mixture is directly sintered at high temperature to obtain lithium-rich lithium iron oxide coated with carbon source and non-metallic oxide at the same time, so that the coating is more uniform during the electrode slurry coating process than the lithium-rich lithium iron oxide itself.
[0009] In the above method, the prepared lithium-rich lithium ferrite only needs to be mixed with a carbon source and a non-metallic oxide and sintered. During the high-temperature treatment process, the non-metallic oxide can react chemically with residual alkali such as Li2O or LiOH on the surface of LFO to reduce the residual alkali on the surface. The carbon source has an increased specific surface area after carbonization and is easier to combine with a non-aqueous solvent, so that the obtained product is easier to coat than the raw material and more uniform after coating, which greatly facilitates subsequent electrochemical performance testing. In addition, its air stability performance is significantly improved.
[0010] Preferably, the content of the carbon source added to the mixture is 0.5% to 5% by weight, and the content of the non-metallic oxide is 0.1% to 2% by weight. It is understandable that too high an amount of the carbon source and the non-metallic oxide added will lead to an increase in the resistivity of the material, thereby affecting its electrochemical properties, while too low an amount will lead to incomplete coating and no significant improvement in its air stability.
[0011] Preferably, the carbon source is selected from at least one of phenolic resin, sulfur, polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl pyrrolidone (PVP), polyaniline (PAn), polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EvOH), ethylene-acrylate copolymer (EMA), and ethylene-methyl acrylate copolymer (EMMA).
[0012] Preferably, the non-metallic oxide is selected from at least one of silicon oxide, boron oxide and phosphorus pentoxide.
[0013] Preferably, the mixed material is directly sintered at high temperature in a muffle furnace; the sintering temperature is 400-700°C, and the sintering time is ≥1h, preferably 3-6h. It is understandable that too low a sintering temperature will lead to incomplete carbonization of the carbon source, affecting the coating uniformity; too high a sintering temperature will increase energy consumption.
[0014] Preferably, the surface residual alkali content of the obtained lithium-rich lithium ferrite coated with a carbon source and a non-metallic oxide is less than 1.31% by mass, which is significantly reduced compared to the uncoated material. After the residual alkali content is reduced, the uniformity of the coating process can be effectively improved, which greatly facilitates subsequent electrochemical testing.
[0015] The present invention also provides a positive electrode active material, which is prepared by the method described in any of the above technical solutions and is lithium-rich iron oxide coated with a carbon source and a non-metallic oxide. The lithium-rich iron oxide coated with a carbon source and a non-metallic oxide is more uniformly coated during the electrode slurry coating process than the lithium-rich iron oxide itself.
[0016] The present invention also provides a lithium ion battery prepared by using the positive electrode active material described in the above technical solution.
[0017] Preferably, after the obtained lithium-rich lithium ferrite coated with a carbon source and a non-metallic oxide is exposed to an environment with an air humidity of 15 to 25% for 24 hours, its initial charge specific capacity is still maintained above 690 mAh / g.
[0018] Compared with the prior art, the advantages and positive effects of the present invention are:
[0019] The present invention provides a method for reducing the difficulty of coating lithium-rich lithium iron oxide during the slurry coating process of the electrode. The method creatively uses a carbon source and a non-metallic oxide to simultaneously coat the lithium-rich lithium iron oxide for the first time, thereby solving the problem of agglomeration and a sharp drop in battery performance of pure lithium-rich lithium iron oxide during slurry coating, making it easier to coat and having coating uniformity. In addition, the coating layer of the carbon source and the non-metallic oxide can slow down the water absorption and deterioration of the lithium-rich lithium iron oxide in the air to a certain extent, thereby improving the air stability of the lithium-rich lithium iron oxide. The process is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of element distribution of PVDF-B2O3@LFO material provided in an embodiment of the present invention;
[0021] Figure 2 Schematic diagram of element distribution of PVDF-SiO2@LFO material provided in an embodiment of the present invention;
[0022] Figure 3 A schematic diagram of a pole piece after coating with pure LFO, PAN-SiO2@LFO material, and PVDF-B2O3@LFO material is provided for an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] 0.2 g PVDF, 0.05 g B2O3 and 10 g LFO were placed in a mixer and mixed for 0.5 h to obtain a PVDF-B2O3-LFO mixture;
[0026] The PVDF-B2O3-LFO mixture was placed in a muffle furnace and sintered at 500°C for 3 h under nitrogen protection to obtain the PVDF-B2O3@LFO material.
[0027] In addition, 1 g of PVDF-B2O3@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0028] Example 2
[0029] 0.1 g PVDF, 0.1 g SiO2 and 10 g LFO were mixed in a mixer for 0.5 h to obtain a PVDF-SiO2-LFO mixture;
[0030] The PVDF-SiO2-LFO mixture was placed in a muffle furnace and sintered at 550°C for 1 h under nitrogen protection to obtain the PVDF-SiO2@LFO material.
[0031] In addition, 1 g of PVDF-SiO2@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0032] The element distribution of the lithium iron-rich lithium LFO and the obtained PVDF-SiO2@LFO material used in this embodiment was characterized by scanning electron microscopy (SEM). Figure 1 and 2 As shown, the F element is evenly distributed and has a high degree of overlap with the O and Fe elements. The distribution of both elements is relatively uniform, which indicates that the coating of the carbon source and the non-metallic oxide forms a relatively uniform coating layer.
[0033] Example 3
[0034] 0.5 g PAN, 0.2 g B2O3 and 10 g LFO were mixed in a mixer for 0.5 h to obtain a PAN-B2O3-LFO mixture;
[0035] The PAN-B2O3-LFO mixture was placed in a muffle furnace and sintered at 500°C for 3 h under nitrogen protection to obtain the PAN-B2O3@LFO material.
[0036] In addition, 1 g of PAN-B2O3@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0037] Example 4
[0038] 0.2 g PAN, 0.05 g SiO2 and 10 g LFO were mixed in a mixer for 0.5 h to obtain a PAN-SiO2-LFO mixture;
[0039] The PAN-SiO2-LFO mixture was placed in a muffle furnace and sintered at 500°C for 3 h under nitrogen protection to obtain the PAN-SiO2@LFO material.
[0040] In addition, 1 g of PAN-SiO2@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0041] Example 5
[0042] 0.5 g PAN, 0.02 g P2O5 and 10 g LFO were mixed in a mixer for 0.5 h to obtain a PAN-P2O5-LFO mixture;
[0043] The PAN-P2O5-LFO mixture was placed in a muffle furnace and sintered at 300°C for 1 h under nitrogen protection to obtain the PAN-P2O@LFO material.
[0044] In addition, 1 g of PAN-P2O5@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0045] Example 6
[0046] 0.1 g PVP, 0.2 g SiO2 and 10 g LFO were placed in a mixer and mixed for 0.5 h to obtain a PVP-SiO2-LFO mixture;
[0047] The PVP-SiO2-LFO mixture was placed in a muffle furnace and sintered at 600 °C for 5 h under nitrogen protection to obtain the PVP-SiO2@LFO material.
[0048] In addition, 1 g of PVP-SiO2@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0049] Example 7
[0050] 0.5 g PVP, 0.05 g B2O3 and 10 g LFO were placed in a mixer and mixed for 0.5 h to obtain a PVP-B2O3-LFO mixture;
[0051] The PVP-B2O3-LFO mixture was placed in a muffle furnace and sintered at 500 °C for 3 h under nitrogen protection to obtain the PVP-B2O3@LFO material.
[0052] In addition, 1 g of PVP-B2O3@LFO material was exposed to an environment with an air humidity of 15-25% for 24 h.
[0053] Comparative Example 1
[0054] Uncoated lithium iron oxide (LFO) material.
[0055] In addition, 1 g of LFO material was taken and exposed to an environment with an air humidity of 15-25% for 24 hours.
[0056] Comparative Example 2
[0057] 0.2 g of glucose and 10 g of LFO were placed in a mixer and mixed for 0.5 h to obtain a C-LFO mixture;
[0058] The C-LFO mixture was placed in a muffle furnace and sintered at 500 °C for 3 h under nitrogen protection to obtain the C@LFO material.
[0059] In addition, 1 g of C@LFO material was taken and exposed to an environment with an air humidity of 15-25% for 24 h.
[0060] Comparative Example 3
[0061] 0.2 g SiO2 and 10 g LFO were placed in a mixer and mixed for 0.5 h to obtain a SiO2-LFO mixture; the SiO2-LFO mixture was placed in a muffle furnace and sintered at 600° C. for 2 h under nitrogen protection to obtain a SiO2@LFO material.
[0062] In addition, 1 g of SiO2@LFO material was taken and exposed to an environment with an air humidity of 15-25% for 24 hours.
[0063] Comparative Example 4
[0064] 0.6g PVP, 0.3g B2O3 and 10g LFO were placed in a mixer and mixed for 0.5h to obtain a PVP-B2O3-LFO mixture:
[0065] The PVP-B2O3-LFO mixture was placed in a muffle furnace and sintered at 350°C for 1 h under nitrogen protection to obtain the PVP-B2O3@LFO material.
[0066] In addition, 1 g of PVP-B2O3@LFO material was taken and exposed to an environment with an air humidity of 15-25% for 24 h.
[0067] Performance Testing
[0068] The materials provided in the above embodiments and comparative examples are used as positive electrode active materials of lithium ion batteries, and the batteries are assembled as follows:
[0069] Preparation of positive electrode sheets: Conductive agent Super-P, adhesive PVDF, and positive electrode active material are dispersed in solvent N-methylpyrrolidone in a mass ratio of 10:10:80, mixed evenly to form positive electrode slurry, and then the positive electrode slurry is evenly coated on the current collector aluminum foil. After drying, rolling, die-cutting, and drying, the lithium-supplemented positive electrode sheet is obtained.
[0070] The electrodes after coating with pure LFO, PAN-SiO2@LFO material, and PVDF-B2O3@LFO material were observed. Figure 3 As shown, pure lithium iron oxide is in the form of colloids, while PAN-SiO2@LFO material and PVDF-B2O3@LFO material are in the form of smooth ink when coated, which is better than pure LFO.
[0071] The negative electrode directly uses lithium sheets.
[0072] Assemble button batteries using the lithium-supplemented positive electrode sheet, negative electrode sheet, separator, gasket and shrapnel, and leave them to stand for 24 hours before use.
[0073] After the battery is assembled, test its initial charge and discharge capacity as follows:
[0074] The battery was charged to 4.5V at 0.05C constant current, and then discharged to 2.5V at 0.05C constant current, and the initial charge and discharge efficiency of the battery was observed.
[0075] The battery performance test results of the embodiments and comparative examples are shown in Table 1.
[0076] Table 1 Battery performance test results
[0077]
[0078] Combined with the data in Table 1, it can be seen that after exposure to non-metallic oxides and carbon for 24 hours, the capacity remains at 690 mAh / g, which is better than that of pure LFO and simply carbon-coated LFO. This indicates that the materials coated with non-metallic oxides and carbon have better air stability.
[0079] Alkalinity test
[0080] The positive electrode lithium supplement products of the above-mentioned Examples 1-7 and Comparative Examples 1-4 were dissolved in methanol at a ratio of solid: liquid = 1:20, and the solid material was filtered out after stirring for 10 minutes. The filtrate was transferred to a titration cup and electrochemically titrated with 0.1M hydrochloric acid standard solution. The sum of the two breakpoints was taken as the total base number. The test results are shown in Table 2:
[0081] Table 2 Surface residual alkali results of Examples 1-7 and Comparative Examples 1-4
[0082] Total base number / % Example 1 0.79 Example 2 0.88 Example 3 1.24 Example 4 1.31 Example 5 1.43 Example 6 1.25 Example 7 1.18 Comparative Example 1 9.35 Comparative Example 2 1.83 Comparative Example 3 2.02 Comparative Example 4 1.17
[0083] As can be seen from Table 2, by comparing Examples 1 to 7 with Comparative Example 1, the alkalinity values of the embodiments are all around 1.31%, which is about 8.04% lower than that of Comparative Example 1, and the reduction effect is obvious; compared with Comparative Examples 2-3, the alkalinity values of Examples 1-7 are also partially reduced, but the carbon source coating wraps the residual alkali therein, which also has a certain effect on reducing the alkalinity value, but the wrapping therein has a certain effect on its electrochemical performance. Although the non-metallic oxide reacts with the residual alkali on the surface, the surface alkalinity value and coating effect are slightly worse than the carbon source and non-metallic oxide coating; compared with Comparative Example 4, although the alkalinity value of Comparative Example 4 is lower, due to the excessive coating amount, its electrochemical performance is slightly worse than that of Examples 1-7.
Claims
1. A method for reducing the difficulty of coating lithium-rich lithium iron oxide during the slurry coating process of the pole piece, characterized in that: The following steps are involved: In a special environment where the air humidity is below 10%, the prepared lithium-rich lithium ferrite is mixed only with a carbon source and a non-metallic oxide to obtain a mixed material. The above mixture is directly sintered at high temperature to obtain lithium-rich lithium iron oxide coated with carbon source and non-metallic oxide at the same time, so that the coating is more uniform during the electrode slurry coating process than the lithium-rich lithium iron oxide itself.
2. The method according to claim 1, characterized in that Measured by weight percentage, the carbon content of the lithium-rich lithium ferrite itself is 0.5% to 5%.
3. The method according to claim 2, characterized in that Calculated by weight percentage, the content of the carbon source added to the mixture is 0.5% to 5%, and the content of the non-metallic oxide is 0.1% to 2%.
4. The method according to any one of claims 1 to 3, characterized in that: The carbon source is selected from at least one of phenolic resin, sulfur, polyacrylonitrile, polyvinylidene fluoride, polyvinyl pyrrolidone, polyaniline, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, ethylene-acrylate copolymer and ethylene-methyl acrylate copolymer.
5. The method according to any one of claims 1 to 3, characterized in that: The non-metallic oxide is selected from at least one of silicon oxide, boron oxide and phosphorus pentoxide.
6. The method according to claim 1, characterized in that The mixed material is directly sintered at high temperature in a muffle furnace; the sintering temperature is 400-700° C., and the sintering time is ≥1 hour, preferably 3-6 hours.
7. The method according to any one of claims 1 to 6, characterized in that: The surface residual alkali content of the obtained lithium-rich lithium ferrite coated with carbon source and non-metal oxide is less than 1.31% by mass.
8. A positive electrode active material, characterized in that The lithium-rich iron oxide coated with a carbon source and a non-metallic oxide is prepared by the method according to any one of claims 1 to 7, wherein the lithium-rich iron oxide coated with a carbon source and a non-metallic oxide is more uniformly coated during the electrode slurry coating process than the lithium-rich iron oxide itself.
9. A lithium-ion battery, characterized in that The positive electrode active material is prepared by using the positive electrode active material described in claim 8.
10. The lithium ion battery according to claim 9, characterized in that: After the obtained lithium iron-rich lithium ferrate coated with a carbon source and a non-metallic oxide is exposed to an environment with an air humidity of 15 to 25% for 24 hours, its initial charge specific capacity is still maintained above 690 mAh / g.
